Do Government Wage Cuts Close Budget Deficits? : A Conceptual Framework for Developing Countries and Transition Economies. (IMF Working Papers; Working Paper, 1996)
Real wage declines have been common in the public sector in many countries over substantial periods of time. In several cases, such wage reductions have coincided with a decline in the efficiency of the public sector. In a simple analytical framework, it is shown that higher wage levels alter the incentive compatible equilibrium by attracting relatively skilled human capital to the government sector, which raises the quality of public output--tax revenue collection in this paper. Increases in wages should be complemented with appropriate monitoring and penalty rates for effective tax administration; prescriptions of raising the statutory tax rate alone, however, may not increase revenue collection.